Kebutuhan Pengguna dalam Perancangan Disain Antarmuka SIMRS RSU ‘Aisyiyah Ponorogo - Rawi Miharti; Dyan Riska Rohmasari (Jurnal Kesehatan Vokasional, 2018)
AbstractBackground: information systems as a technology in managing hospital data are growing rapidly as demands for quality health services.  This is in accordance with regulations that require every hospital to do recording and reporting all hospital activities in the form of SIMRS. The implications of the system development not only have the effect of supporting the improvement of organizational performance, but also a variety of problems that are not as expected of the benefit of SIMRS. One of the problems is that the user needs are not accommodated on the system created. However, in developing an information system, one of the most important elements related to user needs is the design of the interface as a channel for information between the system and its users. RSU 'Aisyiyah Ponorogo has applied SIMRS for several years, but its implementation has not been comprehensive yet. In the daily inpatient census section and hospital reporting activities are still using a manual system that tends to have a high risk of data errors. This becomes a reason to design the interface of the system and its requires in the form of user requirements for the system that is designed. The main stage of building a system is analyzing user needs, specifically identifying the wishes of users who will always interact with the system at all times in supporting their works.Objective: to identify the needs of SIMRS RSU ’Aisyiyah Ponorogo users to design interface, specifically to identify problems in inpatient daily census and hospital reporting activities, users' expectations of the system being built and the data needs of users.Methods: descriptive research with a case study approach. The object of the study was inpatient daily census and hospital reporting activities. The research subjects were 11 people consisting of 1 reporting officer, 8 ward nurses, 1 patient registration officer and 1 hospital technical officer. Techniques of data collection were interview, observation and documented study.Results: the problem of inpatient census section and hospital reporting section is only social patient data obtained during registration can be accessed by census officers or reporting officers. There is still a data filing error on the census sheet in the ward, therefore there is inconsistent data in patient record. System users, especially census officers and reporting officers, need an interactive and familiar interface such as a display on the daily census manual form. While the information that must be displayed is info on patient identity, inpatient info, discharged patient info, ward and index recapitulation. In reporting presentation activities, system must also accommodate the output data in the form of Barber Johnson Graph as healthcare efficient informations.Conclusion: in order to build a useful information system, it is very important to emphasize the participation of users in the developing process. In this stage, the main problems experienced by users in carrying out their work must be identified; as well as solutions that can be given systemically to improve staff performance and improve organizational services. Keywords : analysis of system requirements, user needs, daily census interface design.